PENGARUH LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Nabilah Nur Amalina; Sri Trisnaningsih (Gorontalo State University, 2023)
This research aims to investigate the relationship between financial hardship in manufacturing businesses listed on the IDX and leverage, liquidity, and company size. Manufacturing businesses listed on IDX from 2019 to 2021 make up the population. Quantitative techniques were employed in this investigation with secondary data. Size of the firm, liquidity, and leverage were independent factors in the analysis. Financial hardship is assessed by Earnings Per Share (EPS) for the dependent variable. Over the course of three years, 81 samples from a population of 27 enterprises were produced via purposeful sampling. The analytical method of choice is logistic regression. As a consequence of this research, financial hardship was not influenced by leverage, liquidity, or firm size.